Optimization of the flight technique in ski jumping: The influence of wind - Jung, A.; Müller, W.; Staat, M. (Journal of Biomechanics, 2019)
Ski jumping performance is strongly affected by wind. Flight technique optimization for maximizing jump length is a highly complex motor-control task that also depends on the wind. Pontryagin's minimum principle was used in this study to gain a better understanding on how wind influences flight technique optimization. Optimum time courses of the angle of attack of the skis and of the body-to-ski angle were computed for seven realistic wind scenarios on the large hill and on the flying hill. The optimum values of were smaller at headwind, and larger at tailwind when compared to the optimum time course at calm wind. The optimum values of were the smallest possible ones at the given flight technique constraints, except for the last part of the flight. Optimum adjustments of increased the jump lengths between 0 and 1.8 m on the large hill, and between 0 and 6.4 m on the flying hill. Maximum jump length increases were achieved at the highest headwind speed. Even larger jump length effects can be achieved by using smaller -angles, which might be possible in headwind conditions, but this is associated with increased problems to keep the flight stable.